Where we start: a practical guide to technical communication program administration - Ilyasova, K. Alex, editor; Williams, Sean D., editor; Utah State University Press, publisher (Colorado State University. Libraries, 2026)
Where We Start addresses a gap in the field of technical communication program administration by providing actionable guidance for current & aspiring administrators discussing strategies for program design, curriculum development, assessment, inclusivity, and external partnerships.--Provided by publisher.
Telling your story: strategic planning for technical communication programs / Lee-Ann Kastman Breuch -- Curriculum development in technical communication / Tracy Bridgeford -- Forging strategic links between programmatic identity and institutional action / Bill Williamson -- A taxonomy of programmatic evaluation and research questions to guide TPC program administrators / Joanna Schreiber and Lisa Melonçon -- Building inclusive TPC programs: practical, research-based recommendations / Natasha N. Jones, Kristen R. Moore, and Rebecca W. Walton -- Centering the marginalized: enhancing TPC graduate application processes / Jamal-Jared Alexander -- Mapping your career trajectory / Julie Dyke -- Developing a collaborative graduate UX degree with an engineering college / Andrew Mara -- Growing academic/industry partnerships in technical and professional degree programs: phased approach / Tharon Howard -- Internationalizing the technical communication curriculum: perspectives and approaches for program administrators / Kirk St. Amant -- Epilogue: where we go from here . . . / Sean D. Williams.
Keywords: Communication of technical information -- Study and teaching (Higher); Communication of technical information -- Curricula; Curriculum planning; Technical writing -- Study and teaching (Higher); School administrators -- Vocational guidance